EFFECTIVENESS OF MOBILE LEARNING IN NARRATIVE WRITING AT SECONDARY SCHOOLS (Malaysian Journal of Learning and Instruction, 2025)
Purpose – Mobile learning has several applications that can be advantageous in the field of education. They play a significant role in technology assisted learning. Employing mobile learning in teaching writing skills offers communication, collaboration, and fun learning. It also creates a conducive learning environment among the students. Integration of mobile learning in teaching writing skills allows educators and students to enter the digital era, as the technology used in teaching and learning writing skills via mobile learning is more effective than the conventional approach. Methodology – The mixed-method research design was used to analyse the effectiveness of integrating mobile learning for Form 4 students in Malaysia when they are learning narrative writing skills. A pre-test and a post-test were used to gather quantitative data, while participant observation and focus group interviews were used to collective qualitative data. Findings – The findings elucidated that the students were able to develop their narrative writing skills by using mobile learning as there was an improvement in the post-test when compared with the pre-test. Significance – This study has recommended that mobile learning should be included in teaching various types of writing skills in Malaysian national schools, and appropriate writing materials could be created via mobile learning. Future researchers would need to create a specific writing application which can be employed via mobile learning to enable students to improve in their overall writing skills. This could be a non-conventional teaching method that could be used in the future.